2005
DOI: 10.1038/ng1526
|View full text |Cite
|
Sign up to set email alerts
|

Mutation in myosin heavy chain 6 causes atrial septal defect

Abstract: Atrial septal defect is one of the most common forms of congenital heart malformation. We identified a new locus linked with atrial septal defect on chromosome 14q12 in a large family with dominantly inherited atrial septal defect. The underlying mutation is a missense substitution, I820N, in alpha-myosin heavy chain (MYH6), a structural protein expressed at high levels in the developing atria, which affects the binding of the heavy chain to its regulatory light chain. The cardiac transcription factor TBX5 str… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
180
0
6

Year Published

2006
2006
2021
2021

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 255 publications
(190 citation statements)
references
References 28 publications
4
180
0
6
Order By: Relevance
“…The cross-species alignment of TBX5 protein showed that the altered tryptophan residue is evolutionarily conserved throughout the vertebrates, indicating its functional importance [22]. The understanding of the genetic mutations is an important aspect in deciphering the consequential clinical phenotypes [23,24]. This study was performed to investigate the basis of this divergent phenotype related to a single gene mutation.…”
Section: Discussionmentioning
confidence: 99%
“…The cross-species alignment of TBX5 protein showed that the altered tryptophan residue is evolutionarily conserved throughout the vertebrates, indicating its functional importance [22]. The understanding of the genetic mutations is an important aspect in deciphering the consequential clinical phenotypes [23,24]. This study was performed to investigate the basis of this divergent phenotype related to a single gene mutation.…”
Section: Discussionmentioning
confidence: 99%
“…Different congenital heart malformations (septal defects, patent ductus arteriosus, aortic aneurysm, and Ebstein anomaly) have been reported in families with pathogenic mutations in sarcomeric protein genes, including MYBPC3, MYH6, MYH7, MYH11, and ACTC1. 31,[36][37][38] In children with noncompaction cardiomyopathy, Tsai et al 39 showed that 78% had a congenital heart defect. These data suggest that sarcomeric cardiac muscle proteins are not only involved in cardiomyopathies but also in congenital heart malformations.…”
Section: Discussionmentioning
confidence: 99%
“…Also, mutations in cardiac structural proteins as alpha myosin heavy chain (MYH6) and alpha cardiac actin (ACTC1) were identified in familial CHD (Ching et al, 2005;Matsson et al, 2008). However, so far, only NKX2-5 mutations were reported to cause an atrial septal defect phenotype and development of atrioventricular block (Stallmeyer et al, 2010).…”
Section: Discussionmentioning
confidence: 99%